Ophtalmology emergencies and its management by the general practitioner - Barriga-Salaverry, Guillermo (2019)
Ophthalmological emergencies are sudden situations with imminent risk of vision loss that require immediateattention to avoid permanent sequelae. Some of them must be attended in the first instance by a emergency doctor. The objective of this section is to provide the diagnostic and therapeutic elements so that every physician can perform the task successfully in this instance and derive the situation in a safe and timely manner to the ophthalmologist.